Sustainability in supply chains: An EU-wide solution instead of national rules - Galina V. Kolev; Adriana Neligan (Institut der deutschen Wirtschaft (IW), 2021)
The European Parliament outlines its view for a legislative initiative by the EU Commission for binding supply chain due diligence rules. A European solution is welcome as national rules lead to a diversion of trade barriers and distortions of competition in the internal market. Yet, it is key to define the scope of due diligence so as to avoid negative effects for the EU economy and third countries.
Keywords: 330